A case analysis of the Malaysian Aviation Commission (MAVCOM) in regulating the civil aviation industry / Bashir Ahmad Abdul Majid - Abdul Majid, Bashir Ahmad (2022)
The Malaysian Government established an independent agency named Malaysian Aviation Commission (MAVCOM) to oversee the economic regulation of the industry in response to the requirement of the industry and travelling public. MAVCOM was inaugurated through an Act of Parliament in March 2015. As it is the first time that there is an independent economic regulator for the aviation industry, there is a need to evaluate the performance of MAVCOM, particularly in regard to protecting the interest of the travelling public. The purpose of this research which covered the period up to June 2022 is to determine the performance as well as the public perception of MAVCOM in serving public interest through the decisions made and regulations imposed by MAVCOM in overseeing the economic regulation of the industry. The research method used is qualitative based on a case study of MAVCOM. The case study shows that MAVCOM has performed well in terms of meeting its obligations as provided for in the ACT. Nevertheless, there arose the perception, both from the industry players and the travelling public, that MAVCOM did not meet their respective expectations. Even the Government authority that established MAVCOM in the first place had a differing view with MAVCOM in dealing with some industry issues.